The Effect Of The Learning Model Naval Collaboration Flexible Learning (NCFL) On The Quality Of Education Outcomes: An Innovative Approach To Islamic Religious Education In The Naval College Of Technology: Pengaruh Model Pembelajaran Naval Collaboration Flexible Learning (NCFL) Terhadap Kualitas Hasil Pendidikan: Suatu Pendekatan Inovatif Terhadap Pendidikan Agama Islam Di Naval College Of Technology - Bandono, Adi (Halaqa: Islamic Education Journal, 2020)
The Naval Collaboration Flexible learning (NCFL) learning model is the result of innovation in the field of learning technology to make it more effective, efficient and increase attractiveness in order to achieve learning success. The NCFL learning model was developed by synthesizing various learning and learning theories, system-based, referring to the suitability of the needs and the latest science and technology developments, and still maintaining the distinctive cultural features of the Navy, and based on the values ​​of Pancasila. The problem studied is how the influence of the NCFL learning model in the field of Islamic Religious Education at the Naval College of Technology. The method used is a quantitative method with the process of collecting data through questionnaires to 35 students of the Naval College of Technology and data analysis using SPSS 25.0 software. The results showed that there was a significant influence on the application of the NCFL learning model at the Naval College of Technology, especially in the field of Islamic Religious Education. From the simple linear regression test, the regression equation formula Y = 9.657 + 0.579 X1, meaning that if the X1 value is increased by 1 point, the strength of the Y relationship will increase by the value of the X1 variable, namely 0.579. Furthermore, from the formulation of the regression equation Y = 24.352 + 0.461 X2, which means that if the X2 value is increased by 1 point, the strength of the Y relationship will increase by the value of the X2 variable, namely 0.461. In the multiple linear regression test, the equation formula is Y = 8.274 + 0.476 X1 + 0.187 X2, meaning that if the two variables X1 and X2 are increased by a constant 1, there will be an increase in the Y output value of the X1 and X2 variables, namely (0.476 + 0.187 = 0.663).